2015
DOI: 10.18632/oncotarget.4096
|View full text |Cite
|
Sign up to set email alerts
|

A differentially expressed set of microRNAs in cerebro-spinal fluid (CSF) can diagnose CNS malignancies

Abstract: Central Nervous System malignancies often require stereotactic biopsy or biopsy for differential diagnosis, and for tumor staging and grading. Furthermore, stereotactic biopsy can be non-diagnostic or underestimate grading. Hence, there is a compelling need of new diagnostic biomarkers to avoid such invasive procedures. Several biological markers have been proposed, but they can only identify specific prognostic subtype of Central Nervous System tumors, and none of them has found a standardized clinical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 40 publications
(36 reference statements)
5
62
0
Order By: Relevance
“…It has been reported that tumour cells use glycolysis as their main source of energy, even under aerobic conditions. This phenomenon is called the Warburg effect as it was first described by the Nobel laureate Otto Heinrich Warburg 56. He postulated that tumour cells use glucose for energy and transform it into lactate by the enzyme lactate dehydrogenase 81 84 85.…”
Section: Metabolomicsmentioning
confidence: 99%
“…It has been reported that tumour cells use glycolysis as their main source of energy, even under aerobic conditions. This phenomenon is called the Warburg effect as it was first described by the Nobel laureate Otto Heinrich Warburg 56. He postulated that tumour cells use glucose for energy and transform it into lactate by the enzyme lactate dehydrogenase 81 84 85.…”
Section: Metabolomicsmentioning
confidence: 99%
“…MiR-10 and miR-21 are highly expressed in the cases of GBM and BCBM; however, the miR-200 family can be used to discriminate between GBM and BM [144]. Additionally, miR-223, miR-711, miR-125, and miR-935 signatures were shown to discriminate among medulloblastoma, GBM, breast, and lung cancer BM [156].…”
Section: Mirna and Bcbm Therapeuticsmentioning
confidence: 99%
“…In case of glucose deprivation, hsa-miR-451 expression is reduced, which in turn leads to enhanced cell migration and survival [25]. In a recent study, Drusco et al found that miR-451, among several other miRNAs, is significantly upregulated in cerebrospinal fluid (CSF) sample of glioblastoma patients (>180-fold compared to normal) [26]. These findings are consistent with our results, which indicate that CDC7 inhibition results in upregulation of hsa-miR-451 expression and decreased cell migration.…”
Section: Discussionmentioning
confidence: 99%